Standardized terminological services enabling semantic interoperability between distributed and heterogeneous systems - Ingenerf, Josef; Reiner, J; Seik, Bettina (International journal of medical informatics, 2001)
The interconnection of heterogeneous computer applications in medicine raises the issue of semantic interoperability, going beyond traditional approaches of terminological standardization in basically three aspects. First, the variety of medical vocabularies that currently coexist in different domains is a major barrier for the integration of autonomously developed applications. Fortunately, with the Unified Medical Language System (UMLS) there are machine-readable terminological sources that cover and integrate most of the existing medical vocabularies. Second, the exchanged data need to be processed by a machine for different purposes like patient data integration, access to literature and knowledge bases as well as clinical audit and research. Medical vocabularies provided as passive dictionaries are no longer sufficient. Software system developers should take advantage of terminological services for refining user queries, for mapping the user's terms to appropriate medical vocabularies etc. Third, the services should be accessible uniformly and transparently. In the CORBAmed initiative a proposal for a standardized interface for querying and accessing computerized medical terminology resources was created. Based on the mentioned principles the MUSTANG system (Medical UMLS based Terminology Server for Authoring, Navigating and Guiding the Retrieval to Heterogeneous Knowledge Sources) has been developed. It is implemented on a Windows NT platform using the ORACLE database management and development software. The terminological services are accessible via multiple interfaces. The MUSTANG-System and the experiences with using terminological services in practice are described. Opposed to other levels of standardization like syntactical message standards there is much more a hesitation in the use of standardized terminology.
Keywords: Humans; Medical Audit; Medical Records Systems, Computerized; Quality Control; Semantics; Software; Terminology as Topic; Unified Medical Language System; User-Computer Interface